Sintesis Hidroksiapatit Dari Cangkang Telur Dengan Metode Presipitasi - Novika Sri Wardani; Ahmad Fadli; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Hydroxyapatite powder from eggshell waste as biomaterial has been succesfully synthesized using precipitation method with variation of ratio Ca/P and reaction temperature. High incidence of bone destruction in Indonesia led to an increased need for biomaterials as bone substitute forexample is HAp. The purpose of this study is to assess the effect of the molar ratio of Ca / P and the temperature reaction to hydroxyapatite and characterization of eggshells using AAS and products with XRD, SEM – EDX, and FTIR. Eggshell was calcined at temperature 1000°C to produce calcium oxide (CaO). CaO dissolved in nitric acid (HNO3) to produce Ca(NO3)2 then mixed gently with diammonium hydrogen phosphate was dissolved into aquabidest . HAp produced has ratio Ca/P <1,67. Absorption band of OH-, CO32-, and PO43- groups indicate HAp compounds, but it also contained carbonated hydroxyapatite (CHAp) and tricalcium phosphate (TCP) group. The morphology of HAp particle have a granular shape. The particle size of HAp is getting smaller with increasing the ratio of Ca/P in the range of 69-53 nm and greater with increasing reaction temperature which ranges from 39-47 nm. Keywords : Calcination, eggshell, Hydroxyapatite, precipitation